2008
DOI: 10.1021/la801824c
|View full text |Cite
|
Sign up to set email alerts
|

Bond-Strengthening in Staphylococcal Adhesion to Hydrophilic and Hydrophobic Surfaces Using Atomic Force Microscopy

Abstract: Time-dependent bacterial adhesion forces of four strains of Staphylococcus epidermidis to hydrophobic and hydrophilic surfaces were investigated. Initial adhesion forces differed significantly between the two surfaces and hovered around -0.4 nN. No unambiguous effect of substratum surface hydrophobicity on initial adhesion forces for the four different S. epidermidis strains was observed. Over time, strengthening of the adhesion forces was virtually absent on hydrophobic dimethyldichlorosilane (DDS)-coated gla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
86
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(91 citation statements)
references
References 23 publications
5
86
0
Order By: Relevance
“…Adhesion forces increased with increasing the contact time to 1 s (280 ± 113 pN; Fig. 2 C and D), indicating that cell-cell bonds strengthen with the duration of adhesion (19,26). Force profiles showed multiple ruptures, unlike the 100-ms curves, which we believe result from the sequential rupture of multiple bonds.…”
Section: Resultsmentioning
confidence: 86%
“…Adhesion forces increased with increasing the contact time to 1 s (280 ± 113 pN; Fig. 2 C and D), indicating that cell-cell bonds strengthen with the duration of adhesion (19,26). Force profiles showed multiple ruptures, unlike the 100-ms curves, which we believe result from the sequential rupture of multiple bonds.…”
Section: Resultsmentioning
confidence: 86%
“…Figure 1a shows an AFM force-distance curve for Staphylococcus epidermidis on glass with multiple peaks in the retraction curve. Considering each adhesion peak as an individual detachment event (2,5,8,10,26,27), each peak provides a specific adhesion force (F) according to equation 1, and the only variable for a given combination of bacterial strain and substratum is the number of short-range bonds (k). It should be noted that it is a tedious task to identify the minor peaks, since it is not clear a priori when a peak should be taken as an individual detachment event.…”
Section: Theoretical Background Of Poisson Analysis Of Adhesion Forcesmentioning
confidence: 99%
“…AFM spectroscopy reveals the distance dependence of the adhesion force, and measured force-distance curves can be compared with theoretical models (3,7,8,13), which are usually based on the Derjaguin-Landau-Verwey-Overbeek (DLVO) theory (12, 39). The extended DLVO theory (36) includes not only long-range LW and EDL interactions, as does the classical DLVO theory, but also short-range AB interactions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21,23,26 Boks et al reported that bond strengthening for four strains of S. epidermidis on a hydrophobic surface was fast and limited to a minor increase, while strengthening of the bonds on a hydrophilic surface increases significantly with contact time. 33 As water molecules adjacent to a hydrophobic surface are not able to form hydrogen bonds with that surface (hydrophobic effect), bacterial adhesion to a hydrophobic specimen is brought about by an entropically favorable release of water molecules. The results of this research indicated that the amount of bacteria that adhered to the more hydrophobic Co-Cr-Mo surface was significantly less than that for the rather hydrophilic CP-Ti surface.…”
Section: Discussionmentioning
confidence: 99%